Sideband cooling of small ion Coulomb crystals in a Penning trap - Stutter,G; Hrmo,P; Jarlaud,V; Joshi,MK; Goodwin,JF; Thompson,RC (Journal of Modern Optics, 2017)
We have recently demonstrated the laser cooling of a single 40 Ca + ion to the motional ground state in a Penning trap using the resolved-sideband cooling technique on the electric quadrupole transition S 1/2 ↔ D 5/2 . Here we report on the extension of this technique to small ion Coulomb crystals made of two or three 40 Ca + ions. Efficient cooling of the axial motion is achieved outside the Lamb-Dicke regime on a two-ion string along the magnetic field axis as well as on two- and three-ion planar crystals. Complex sideband cooling sequences are required in order to cool both axial degrees of freedom simultaneously. We measure a mean excitation after cooling of n COM for the centre of mass (COM) mode and n B for the breathing mode of the two-ion string with corresponding heating rates of 11(2)s -1 and 1(1)s -1 at a trap frequency of 162 kHz. The occupation of the ground state of the axial modes (n tilt = n COM = 0) is above 75% for the two-ion planar crystal and the associated heating rates 0.8(5)s -1 at a trap frequency of 355 kHz.